2020
DOI: 10.1016/j.ajhg.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

eQTL Colocalization Analyses Identify NTN4 as a Candidate Breast Cancer Risk Gene

Abstract: Breast cancer genome-wide association studies (GWAS) have identified 150 genomic risk regions containing more than 13,000 credible causal variants (CCVs). The CCVs are predominantly noncoding and enriched in regulatory elements. However, the genes underlying breast cancer risk associations are largely unknown. Here, we used genetic colocalization analysis to identify loci at which gene expression could potentially explain breast cancer risk phenotypes. Using data from the Breast Cancer Association Consortium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Its high morbidity and high mortality have attracted the attention of clinicians and scientific researchers. It is a heterogeneous disease, and current researches have found that its occurrence and development were related to numerous genetic changes 2‐4 . A large number of biologically active molecules participate in the regulation of signalling pathways in BC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Its high morbidity and high mortality have attracted the attention of clinicians and scientific researchers. It is a heterogeneous disease, and current researches have found that its occurrence and development were related to numerous genetic changes 2‐4 . A large number of biologically active molecules participate in the regulation of signalling pathways in BC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although a major goal of these studies is to identify new strategies for cancer prevention or treatment, a major obstacle in translating these findings to meaningful biological insights is that most risk variants are non-coding and the gene targets of the associations are not clear. Following fine mapping to identify the CCVs for BC, prioritizing loci with relatively few CCVs, chromatin conformation capture (3C) and luciferase assays, have been performed at 16 BC risk loci implicating regulation of TERT 40 , CCND1 50 , FGFR2 51 , IGFBP5 52 , MAP3K1 53 , ESR1, RMND1 and CCDC170 41 , KLF4 54 , NRBF2 55 , ABHD8 56 , FGF10 and MRPS30 57 , KLHDC7A, PIDD1, CITED4, PRKRIP1 and RASA4 4 , DUSP4 28 , NTN4 58 , TBX3 34 and novel lncRNAs, CUPID1 and CUPID2 59 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a major obstacle in translating these findings to meaningful biological insights is that the majority of risk variants are non-coding and the gene targets of the associations are not clear. Following fine mapping to identify the CCVs for BC, prioritizing loci with relatively few CCVs, chromatin conformation capture (3C) and luciferase assays, have been performed at 16 BC risk loci implicating regulation of TERT (Bojesen et al, 2013), CCND1 (French et al, 2013), FGFR2 (Meyer et al, 2013), IGFBP5 (Baxter et al, 2021), MAP3K1 (Glubb et al, 2015), ESR1, RMND1 and CCDC170 (Dunning et al, 2016), KLF4 (Orr et al, 2015), NRBF2 (Darabi et al, 2015), ABHD8 (Lawrenson et al, 2016), FGF10 and MRPS30 (Ghoussaini et al, 2016), KLHDC7A, PIDD1, CITED4, PRKRIP1 and RASA4 (Michailidou et al, 2017), DUSP4 (Glubb et al, 2020), NTN4 (Beesley et al, 2020b), TBX3 (Beesley et al, 2020a) and novel lncRNAs, CUPID1 and CUPID2 (Betts et al, 2017).…”
Section: Discussionmentioning
confidence: 99%